2017
DOI: 10.1130/g38547.1
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical climate conditions and mangrove growth in Arctic Siberia during the early Eocene

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 31 publications
13
80
0
Order By: Relevance
“…A thorough review of Quaternary Cedrus records (pollen grains and macroremains) in Southern Europe was provided by Magri (2012) and completed by Magri et al (2017), leading to a reconstruction of its history around the Mediterranean Basin. A few Cedrus pollen grains have been recorded on both sides of the Arctic Ocean, in the New Siberian Islands (Suan et al, 2017) and the Mackenzie Delta (Salpin et al, accepted) where it confirms a first presence, observed by Rouse & Srivastava (1972), during cooler phases surrounding the early Eocene Climatic Optimum, i.e. at 58 -54 Ma and 50 -38 Ma (Suc, unpublished).…”
Section: Microtropis Fallax Pitard (Celastraceae)mentioning
confidence: 85%
“…A thorough review of Quaternary Cedrus records (pollen grains and macroremains) in Southern Europe was provided by Magri (2012) and completed by Magri et al (2017), leading to a reconstruction of its history around the Mediterranean Basin. A few Cedrus pollen grains have been recorded on both sides of the Arctic Ocean, in the New Siberian Islands (Suan et al, 2017) and the Mackenzie Delta (Salpin et al, accepted) where it confirms a first presence, observed by Rouse & Srivastava (1972), during cooler phases surrounding the early Eocene Climatic Optimum, i.e. at 58 -54 Ma and 50 -38 Ma (Suc, unpublished).…”
Section: Microtropis Fallax Pitard (Celastraceae)mentioning
confidence: 85%
“…Weller & Stein, 2008). There are, however, some TEX 86 -based SST values Sluijs et al, 2008) that show surprisingly low values of 8-13°C for the EECO; that is, they are about 10°C lower than the U K 37 -SST values from close-by depth intervals (Figure 15; Table 1), a difference that is very similar to the Arctic seasonal temperature variability (Basinger et al, 1994;Greenwood & Wing, 1995;Suan et al, 2017;Wolfe, 1994). Thus, one possible explanation for this discrepancy could be that these TEX 86 -SST values represent more the winter SST (for further details and discussion, see Weller & Stein, 2008), further supporting year-round ice-free conditions in the central Arctic Ocean under this extreme warmth.…”
Section: 1029/2018pa003433mentioning
confidence: 86%
“…As the alkenone‐producing coccolithophorids need sunlight for photosynthesis, the alkenone SST represents the summer SST. Then, considering the strong seasonal temperature variability of >10 °C during the early‐middle Eocene (Basinger et al, ; Wolfe, ; Greenwood & Wing, ; Suan et al, ; see Weller & Stein, , for more detailed discussion of ACEX alkenone data and references), favorable conditions for sea‐ice formation may have occurred during winter time. That means, after about 46.3 Ma (or 41.7 Ma according to Age Model 2), the environmental conditions in part of the Arctic Ocean might have been similar to that observed in the modern Baltic Sea where summer SSTs >15 °C and winter SSTs <1 °C with sea‐ice formation are typical (Krause, ; Schmelzer & Holfort, ; Wüst & Brögmus, ).…”
Section: Long‐term Climate Change From Greenhouse To Icehouse Conditionsmentioning
confidence: 99%
“…Seasonal ranges are estimated from 2°-3° C to 20° C and an annual precipitation of 120 cm/yr (Eberle and Greenwood, 2012). Similar conditions, including mangrove swamps, were circumpolar at approximately the same paleolatitudes in present-day Siberia (Suan et al, 2017). Not only did the polar warmth facilitate dispersal and spread of Laurasian biotas, but, given the direct and wellestablished relationship between area and species diversity (MacArthur and Wilson, 1963;Lomolino, 2000), the expansion of earth's habitable landmass must have vastly increased the diversification of all life, not just mammals.…”
Section: Introductionmentioning
confidence: 87%